Treasury Control in the Budget Process and Prospects for its Development - Eshnazarov S.T (Genius Publishing Group, 2023)
In this article, treasury control in the state financial control system in the budgeting process, its essence and tasks, shortcomings of the system, issues of its development are described. In this, the main focus is on treasury control, the need to improve its effectiveness in the budget process, and its specific features are shown.
Keywords: Budget process; treasury control; internal audit; initial